Animal source foods and nutrition of young children: an ex ante analysis of impact of HPAI on nutrition in Indonesia - Iannotti, Lora L.; Barron, Manuel; Roy, Devesh (International Food Policy Research Institute, 2008)
One aspect of livelihood in developing countries that has been largely neglected is the effect of highly pathogenic avian influenza (HPAI) disease, prevention, and control strategies on nutrition. An HPAI outbreak could have income and price effects that could influence the consumption of all food commodities and hence, the nutrition of household members. Perhaps more importantly, an HPAI outbreak could lead to discrete changes in preferences away from poultry, leading to a consumption shock of poultry products.